Pengaruh Metode Bandongan Terhadap Kemampuan Tahsin dan Tahfidz Al-Qur’an - Siti Maisyaroh (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
The purpose of the research is to : 1) Knowing whether there is an effect of using the bandongan method on the tahsin Al’quran students ability in the Madrasah Diniyah Awaliyah Miftahul Ulum, 2) Knowing whether there is an effect of using the bandongan method on the tahfidz Al Qur’an students in the Madrasah Diniyah Awaliyah Miftahul ulum. 3) Knowing whether there is an effect of using a bandongan method on the students’ ability of tahsin and tahfidz Al Qur’an students ability in the madrasah Diniyah Miftahul ulum. The type of experimental research used is Quasi Experimental Research with Nonequivalent Control Group Design. The research subjects consisted of 52 students as the study population. Collecting data using observation, documentation and oral test (pretest and posttest). The hypothesis testing is done by t-test using independent sample test and f test using One Way Anova to find out whether there is a significant effect of using the bandongan method on the ability of tahsin and tahfidz Al Qur’an. Based on the results of the discussion about the use of the bandongan method, it has no effect on the ability of tahsin and tahfidz Al-Qur’an. This is evidenced by the results of the independent t-test data analysis sample test of the ability of the Qur’anic tahsin at the 5% significance level, the calculated significance value is greater than 0.05, namely 0.526 and the ability of the Qur’anic tahfidz is obtained a greater significance value. from 0.05 to 0.283. Analysis of the f One Way Anova test data with a significance level of α = 0.05, namely sig. 0.592 ≥ 0.05 shows that there is no significant effect of using the bandongan learning method on the ability of tahsin and tahfidz Al-Qur’an.